IN ISLAM FAMILY AND OF MARRIAGE IMPORTANCE - Зокирова Раъно Ислом қизи (Bright Mind Publishing, 2025)
Family every one human in life win important is the gallows. If the family peace - harmony, each other relatively If you live with love, you will reach that place. of Allah blessing it is oiled. In this article Uzbek family’s moral religion is a factor in their relationships and religious your upbringing importance about word conducted.
Keywords: Family, society socio-spiritual suffocation, feelings, worldview, thinking, society, woman, human divine, divine instructions, men, women.